Pembinaan Pegawai Negeri Sipil pada Dinas Pendidikan dan Kebudayaan Kabupaten Lima Puluh Kota - Resi Rahma Dini; Ermita Ermita; Nelitawati Nelitawati; Jasrial Jasrial (Journal of Educational Administration and Leadership, 2021)
The points of this study are to obtain data and information regarding the development of civil servants in the education and cultural offices of fifty cities, namely (1) Knowledge Development, (2) Attitude Development, (3) Activity motivation renewal, (4) Activity environment renewal, (5) skills renewal. a descriptive study of a quantitative approach. The study population numbered 85 employees and the sample size was determined using the Taro Yamane formula by means of Proportional Random Sampling of 54 employees. The study instrument was a Likert scale model questionnaire. The results of data analysis show that the development of civil servants in the Education and Culture Office of Fifty Cities Regency has been considered good with the acquisition level of 3.60 with the following explanation; (1) knowledge development has an effect on the good category, namely the achievement of 4.13, (2) the development of attitude influences the good category is obtained 3.74, (3) the development of morale has an effect on a sufficient level, namely 3.26, (4) work discipline coaching has an effect on a good level, namely on the acquisition of 4.03, (5) skills development is at a sufficient level, namely at the acquisition of 2.86. In general, it can be concluded that the development of civil servants at the Education and Culture Office of Fifty Cities is in the good category with an average score of 3.60. However, the coaching must be optimized again for optimal work results.